SEARCHING FOR (AND FINDING) NEOCOLONIAL FANTASIES: SEXUALIZATION OF WOMEN FROM THE GLOBAL SOUTH AND THE GLOBAL EAST IN GOOGLE’S TEXT SEARCH RESULTS - Urman, Aleksandra; Makhortykh, Mykola (AoIR Selected Papers of Internet Research, 2023)
Search engines serve as information gatekeepers on a multitude of topics dealing with different aspects of society. However, the ways search engines filter and rank information are prone to biases related to gender, ethnicity, and race. In this paper, we conduct a systematic algorithm audit to examine how one specific form of misrepresentation bias, namely, sexualization, is manifested in Google’s text search results about different national and gender groups. We find evidence of sexualization of women, particularly those from the Global South and East in search outputs. This is amplified by contextual advertisements pushed by Google in response to different search queries.